2002
DOI: 10.1016/s0010-938x(02)00004-5
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of 304 stainless steel in high temperature, hydrogenated water

Abstract: The corrosion behavior of an austenitic stainless steel (UNS S30400) has been characterized in a 10,000 hour test conducted in hydrogenated, ammoniated water at 260°C. The corrosion kinetics were observed to follow a parabolic rate dependency, the parabolic rate constant being determined by chemical descaling to be 1.16 mg dm-* h r -l h . X-ray photoelectron spectroscopy, in combination w i t h argon ion milling and target factor analysis, was appIied to provide an independent estimate of the rate constant tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(73 citation statements)
references
References 12 publications
4
65
1
1
Order By: Relevance
“…0.2 vs. 0.1). This result is consistent with previous analyses [3,5] which indicate that the outer layer corrosion films on nickel base NiCrFe alloys contain a higher percentage of Cr(III) than those on stainless steels, i.e., n = 0. …”
Section: Primitive Mixing Modelsupporting
confidence: 93%
See 1 more Smart Citation
“…0.2 vs. 0.1). This result is consistent with previous analyses [3,5] which indicate that the outer layer corrosion films on nickel base NiCrFe alloys contain a higher percentage of Cr(III) than those on stainless steels, i.e., n = 0. …”
Section: Primitive Mixing Modelsupporting
confidence: 93%
“…Lattice parameters of the (cubic) spinel phases, determined from a whole pattern fit of XRD peak positions for five high angle reflection planes: [9,3,1], [8,4,4], [10,2,0], [9,5,1] and [10,2,2], are compared in Table I. Also included in Table I are the peak widths (full width at half maximum, FWHM) of the [8,4,4] peak.…”
Section: Single Phase Annealingmentioning
confidence: 99%
“…In the 1980s, working on stainless steels, Robertson [85] mentioned that the inner layer was Cr-enriched and consisted of a chromite spinel rather than chromine Cr 2 O 3 . These observations were detailed twenty year later by Ziemniak [86] showing that the inner layer was composed of a fcc spinel with a stochiometry close to (Ni 0. almost pure magnetite Fe 3 O 4 and more recently, Terachi [87] showed that they were AB 2 O 4 spinel (A and B = Fe, Cr and Ni). The effects of chromium and minor elements, cold-work, water chemistry and heat treatments rather than the oxidation mechanism itself were also studied [84,85].…”
Section: State Of the Artmentioning
confidence: 96%
“…Another way to clarify the mechanism underlying SCCby characterizing the oxide films formed on austenitic stainless steels has been carried out for many years, [10][11][12][13][14][15][16][17] because the chemical and physical properties of oxide films are thought to play important roles in the cracking process, especially in its initiation stage. [18][19][20] According to the results of those studies, oxide film formed on stainless steel in hightemperature water has a double-layer structure.…”
Section: Introductionmentioning
confidence: 99%